-m+3=m-7

Simple and best practice solution for -m+3=m-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -m+3=m-7 equation:



-m+3=m-7
We move all terms to the left:
-m+3-(m-7)=0
We add all the numbers together, and all the variables
-1m-(m-7)+3=0
We get rid of parentheses
-1m-m+7+3=0
We add all the numbers together, and all the variables
-2m+10=0
We move all terms containing m to the left, all other terms to the right
-2m=-10
m=-10/-2
m=+5

You can always share this solution

See similar equations:

| 3x+12=3x+25 | | 4x^-3+1=0 | | 6.4g+4=3.4g+10 | | -10d-1+3D=-d-1 | | 2.8/x=35 | | 8+f=-5f-10 | | 8-5h=-9h | | 5+8=18(3?x)?5+8=18 | | 3x+2(-12)=64 | | -4.1=8.7+y/8 | | 4x+14=5x+4=6x-3 | | -4.1=8.7=y/8 | | 2l+8=12 | | 77-3a=44 | | 2.7x=1.62 | | 5+19x?7?26x=?51 | | 5x+-10=3x+30 | | y+2(2.5)=15 | | 12(x-0,5)=4x-34 | | 10x+20/15=6 | | 4*x-13=-9 | | 3*x-6,2=5,8 | | 3*x-11=-20 | | -0.48x=1.2 | | 5*x+2,7=17,7 | | 17=4*x+9 | | 59=7b-8 | | 5*x-28=37 | | 7*x+22=85 | | 3*x+17=35 | | 1/2(p+16)=13 | | 8*x-11=45 |

Equations solver categories